Data Sheet 1_Development and validation of the FAAP model for prognostic stratification in HCC patients treated with TACE, sintilimab plus bevacizumab: a multicenter study.docx - Liying Ren (11143129) (2025)
Introduction Although the transcatheter arterial chemoembolization (TACE) combined with sintilimab and bevacizumab improves outcomes in unresectable HCC (uHCC), predictive tools are lacking. This study developed and validated a prognostic model for triple therapy efficacy. Methods A multicenter study enrolled uHCC patients receiving TACE-sintilimab-bevacizumab. Overall survival (OS) was the primary endpoint; a Cox model was developed and validated. Results This study enrolled 147 patients (training cohort: n = 92; validation cohort: n = 55). The optimal cutoff value for the fibrin degradation product-to-cholinesterase ratio*1000 (FCR) was determined as 0.8. Univariate and multivariate Cox regression analyses identified FCR, AST, AFP, and PVTT as independent OS predictors. These variables were integrated to establish the FAAP scoring system, which demonstrated robust discriminative performance with AUC of 0.804 (95% CI: 0.703-0.893) and 0.799 (95% CI: 0.67-0.911) in the training and validation cohorts, respectively. Patients were stratified into three risk groups based on FAAP scores: low (FAAP < 0.7), intermediate (0.7 ≤ FAAP < 2.2), and high (FAAP ≥ 2.2). Kaplan-Meier analyses revealed significant prognostic stratification for both OS and progression-free survival (PFS) across groups. Subgroup analyses confirmed the prognostic relevance of FAAP scores in key clinical subsets, including age, gender, extrahepatic metastasis status, viral hepatitis etiology, PVTT presence, and Child-Pugh stage. Conclusions The FAAP scoring system effectively predicted survival outcomes in HCC patients receiving TACE-sintilimab-bevacizumab therapy, which suggests its clinical utility for prognostic prediction. Further large prospective studies are required for external validation.